High-pressure phases of VO2 from the combination of Raman scattering and ab initio structural search - Baledent, Victor; Cerqueira, Tiago T. F.; Sarmiento-Perez, Rafael; Shukla, Abhay; Bellin, Christophe; Marsi, Marino; Itie, Jean-Paul; Gatti, Matteo; Marques, Miguel A. L.; Botti, Silvana; Rueff, Jean-Pascal (Physical Review B, 2018)
Despite more than 50 years of investigation, the understanding of the metal-insulator transition in VO2 remains incomplete and requires additional experimental and theoretical works. Using Raman scattering under pressure, we first confirm the known transition around 11 GPa affecting the V orbital occupancy in the absence of structural changes. Moreover, we disclose a transition around 19 GPa involving the V orbitals together with a structural distortion, revealed by the splitting of a phonon branch associated with the V chains. The high-pressure metallic X phase is found to be of low symmetry and becomes the lowest-enthalpy structure at high pressure by ab initio structural prediction calculations. In contrast to a well-established picture of the metal-insulator transition (i.e., the Peierls transition), the high-pressure metallic phase here is of lower symmetry than the ambient pressure insulating phase.
CRIS-Team Scopus Importer:2023-04-20